The Impact Of Sports Outside Of School On Physical Education Learning In Primary School - Muhammad Bayu Pamungkas; Lazuardy Akbar Fauzan; Aryadi Rachman (UNIB Press, 2025)
The purpose of this study is to examine the impact of student involvement in sports activities outside of formal learning hours on the effectiveness of Physical Education, Sports, and Health (PJOK) learning in elementary schools. Using the quantitative association method with a sample of 6th grade students of Primary School 1 Guntung Manggis, data was obtained through a questionnaire that had been validated and analyzed using SPSS 25. The results of the study revealed that there was a strong and significant relationship between student participation in sports activities outside school and their level of involvement in PJOK learning. Students who actively participate in sports outside stated that the level of involvement and activeness in PJOK learning was higher compared to students who were inactive. This research provides important recommendations for schools and sports clubs as building positive things in supporting student development.